A new species of Ereymatermes Constantino (Isoptera, Termitidae, Nasutitermitinae) from the northeastern Atlantic Forest, Brazil - Eliana M. Cancello; Carolina Cuezzo (Papéis Avulsos de Zoologia, 2007)
Ereymatermes Constantino is a nasute genus endemic to the Neotropical region, which included Ereymatermes rotundiceps Constantino from the forest of the lower Japurá River, AM, Brazil, and E. panamensis Roisin from the Panama Canal area. Herein Ereymatermes piquira, a new species from the northeastern Atlantic Forest, is described and illustrated based on the soldier and worker castes. The meaning of the two types of workers ("worker with broad gap" and "worker with narrow gap") and its relation to feeding habits are discussed. Ereymatermes Constantino é um gênero endêmico da região Neotropical e continha as espécies Ereymatermes rotundiceps Constantino, descrita da floresta do baixo Rio Japurá, AM, e E. panamensis Roisin descrita da área do Canal de Panamá. Aqui, Ereymatermes piquira, uma nova espécie da Mata Atlântica do nordeste é descrita e ilustrada a partir de soldados e operários. O significado dos dois tipos de operários ("operário com intervalo amplo" e "operário com intervalo estreito") e sua relação com hábitos alimentares são discutidos.